Ferroelectrics in Microwave Devices, Circuits and Systems Physics, Modeling, Fabrication and Measurements - Gevorgian, Spartak. (Engineering Materials and Processes, 2009)
Todays wireless communications and information systems are heavily based on microwave technology, as are an increasing number of other industry sectors. Extensive research has been carried out into the development of new technologies to meet the increasingly complex requirements of such systems. Among these new technologies agile (tuneable, reconfigurable, and adaptable) microwave components based on ferroelectric materials, have great potential and are already gaining ground. Ferroelectrics in Microwave Devices, Circuits and Systems is an introduction to the field. It explores the emergence of new functionalities and components with enhanced performance that can meet the agility and cost requirements of modern microwave-based systems. The book provides the reader with practical knowledge in a range of areas, including: " physics, " fabrication technology, " methods of design, " modeling, and " measurement of ferroelectric components and devices. Ferroelectrics in Microwave Devices, Circuits and Systems is a useful research tool for both graduate and undergraduate students, as well as designers of microwave devices, circuits, and systems. The Engineering Materials and Processes series focuses on all forms of materials and the processes used to synthesise and formulate them as they relate to the various engineering disciplines. The series deals with a diverse range of materials: ceramics; metals (ferrous and non-ferrous); semiconductors; composites, polymers, biomimetics etc. Each monograph in the series is written by a specialist and demonstrates how enhancements in materials and the processes associated with them can improve performance in the field of engineering in which they are used.